2016
DOI: 10.1038/hdy.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Few genetic and environmental correlations between life history and stress resistance traits affect adaptation to fluctuating thermal regimes

Abstract: Few genetic and environmental correlations between life history and stress resistance traits affect adaptation to fluctuating thermal regimes T Manenti, JG Sørensen, NN Moghadam and V Loeschcke Laboratory selection in thermal regimes that differed in the amplitude and the predictability of daily fluctuations had a marked effect on stress resistance and life history traits in Drosophila simulans. The observed evolutionary changes are expected to be the result of both direct and correlated responses to selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…These data clearly demonstrate that evolutionary processes are distinct in fluctuating and constant temperature environments. Recent work on the insect, Drosophila simulans, draws similar conclusions (Manenti et al, 2016).…”
Section: Experimental Evolutionsupporting
confidence: 49%
See 1 more Smart Citation
“…These data clearly demonstrate that evolutionary processes are distinct in fluctuating and constant temperature environments. Recent work on the insect, Drosophila simulans, draws similar conclusions (Manenti et al, 2016).…”
Section: Experimental Evolutionsupporting
confidence: 49%
“…heat shock survival or in tolerance curve parameters (Scheiner, 1993;Kellermann et al, 2009;Ketola et al, 2014;Kristensen et al, 2015). However, as stated here the adaptive benefit of heritable variation in some proxy of fitness in a constant environment might be minor in fluctuating environments if it is not genetically correlated with fitness in fluctuating environments (Ketola et al, 2014;Manenti et al, 2016). What is crucially missing in most quantitative genetic experiments performed so far is correlating the abovementioned proxies to fitness in fluctuating environments.…”
Section: Quantitative Genetic Experimentsmentioning
confidence: 95%
“…Fluctuating thermal regimes are suggested to have a greater ecological relevance than constant regimes as they are more representative of natural environments (Klepsatel et al., ; Manenti et al., ). Fluctuating temperatures can yield different results for a variety of traits when compared to constant temperatures (Bozinovic et al., ; Vanin et al., ; Manenti et al., ). Our results showed that longevity differences between heat‐resistant and heat‐sensitive stocks at constant temperatures disappear at fluctuating temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in environmental conditions can change trait interactions differently (Sgrò & Hoffmann, ), and temperature has been shown to affect trait correlations (Norry & Loeschcke, ; Klepsatel et al., ; Manenti et al., ). Furthermore, fluctuating temperatures are expected to demand higher energetic costs (Hoffmann et al., ; Bowler & Terblanche, ), which may result in negative correlations between stress resistance and life‐history traits in flies exposed to fluctuating thermal regimes (Manenti et al., ). In this regard, our results show that the expected genetic correlation between heat resistance and longevity depends on the thermal conditions in which longevity is assayed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of day length for multiple life‐history traits and for the ability to cope with stressful thermal conditions, most experimental studies investigating the ability to perform in environments with variable temperatures have neglected the role of photoperiod and its importance for stress resistance and for shaping the distribution of species (Ketola & Saarinen, ; Kristensen, Kjeldal, Schou, & Lund, ; Manenti, Sørensen, Moghadam, & Loeschcke, ). In the present study, we investigate the importance of seasonal variation in day length on stress resistance and life‐history traits of five populations of Drosophila subobscura distributed across North Africa and Europe spanning the latitudes 31°N to 59°N (Table ).…”
Section: Introductionmentioning
confidence: 99%